Stroke as Initial Manifestation of Adenosine Deaminase 2 Deficiency - Elbracht, Miriam; Mull, Michael; Wagner, Norbert; Kuhl, Christiane; Abicht, Angela; Kurth, Ingo; Tenbrock, Klaus; Häusler, Martin (Neuropediatrics, 2017)
Deficiency of adenosine deaminase 2 (ADA2) due to homozygous or compound heterozygous mutations in the cat eye syndrome chromosome region, candidate 1 (CECR1) gene causes an autoimmune phenotype with systemic vasculitis affecting the skin, inner organs, and the central nervous system. Typically, stroke has been reported to follow systemic inflammatory disease and predominantly affects posterior and central brain areas. Here, we describe one of the rare patients in whom acute mesencephalic stroke preceded systemic inflammation and presented as initial clinical symptom. Symptoms typical for ADA2 deficiency such as fever, livedo racemosa, abdominal colics, arthralgias, and Raynaud phenomenon were observed later. Moreover, angiography of cerebral arteries did not reveal typical vasculitic findings supporting the hypothesis that alternative mechanism of vascular occlusion might have caused the stroke. ADA2 deficiency should be considered in patients with childhood stroke despite the absence of systemic inflammation and cerebral vasculitis.
Keywords: stroke; adenosine deaminase 2 deficiency; CECR1; polyarteritis nodosa; vasculitis; Sneddon syndrome